2022
DOI: 10.36253/a_h-12326
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight and prey species on gut passage time in an endemic gecko Quedenfeldtia moerens (Chabanaud, 1916) from Morocco

Abstract: Gut passage time (GPT), a key factor in digestive procedure, is of pivotal importance for digestion. Several parameters may affect GPT, such as temperature, length of gastrointestinal tract and body size. Here, we examine the influence of prey weight and prey species on GPT in the endemic diurnal gecko Quedenfeldtia moerens, from the Anti-Atlas Mountains in central Morocco. We used two prey species, house crickets (Acheta domesticus, AD) and mealworms (Tenebrio molitor, TM). Lizards were fed with the larval st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Its insect powder enhances food properties such as nutritional value, crispness, taste, and digestibility [ 9 , 12 , 16 , 18 ]. Apart from human nutrition, this species is used as feed for a plethora of organisms such as fish, reptiles, birds, and crustaceans [ 20 , 21 , 22 , 23 , 24 ]. In addition, recent studies revealed that T. molitor extracts display antiproliferative, antimicrobial, antifreeze, antithrombotic, preservative, and healing properties [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its insect powder enhances food properties such as nutritional value, crispness, taste, and digestibility [ 9 , 12 , 16 , 18 ]. Apart from human nutrition, this species is used as feed for a plethora of organisms such as fish, reptiles, birds, and crustaceans [ 20 , 21 , 22 , 23 , 24 ]. In addition, recent studies revealed that T. molitor extracts display antiproliferative, antimicrobial, antifreeze, antithrombotic, preservative, and healing properties [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…En algunos casos, la cola se rompe pero no se separa completamente del cuerpo, dando lugar a una cola regenerada con dos o tres puntas (cola trifurcada) (Pheasey, Smith, Brouard, Atkinson, 2014), e incluso hasta seis, como el caso de Salvator merianae (Pelegrín y Muniz Leão, 2016), siendo la bifurcación mucho más frecuente (86%) que las trifurcaciones (12%) o multifurcaciones (2%) (Barr, Somaweera, Godfrey, Gardner, Bateman, 2020). Barr et al (2020) realizaron una revisión de este tipo de regeneración anómala, registrando su presencia para 22 familias de lagartijas, entre las que se incluyen a Agamidae (Ofori, Martey, Musah, Attuquayefio, 2018), Anguidae (Cozendey, Campos, Lanna, Amorim, Sousa, 2013), Anolidae (Caicedo-Martínez, Mejía-Fontecha, Rojas-Morales, Caicedo-Portilla, Ramírez-Chaves, 2022), Corytophanidae (Nahuat-Cervera y Avilés, 2020), Crotaphytidae (Montanucci, 1969), Diploglossidae (Cozendey et al, 2013), Gekkonidae (Caicedo-Martínez et al, 2022), Gymnophthalmidae (Pheasey et al, 2014), Iguanidae (Caicedo-Martínez et al, 2022), Lacertidae (Kolenda, Wieczorek, Najbar, Najbar, Skawiński, 2017), Liolaemidae (Fernández, Corrales, Valdéz, Acosta, Acosta, 2022), Phrynosomatidae (Mata-Silva, Rocha, Johnson, Wilson, 2013, Phyllodactylidae (Caicedo-Martínez et al, 2022), Scincidae (Miles, Danser, Shoemaker, 2020), Sphaerodactylidae (Mouadi et al, 2021), Sphenodontidae (Seligmann et al, 2008), Teiidae (Caicedo-Martínez et al, 2022) y Tropiduridae (Martins et al, 2013;Passos, Pinheiro, Galdino, Rocha, 2014); entre otras.…”
unclassified